Antimicrobial Activity of Successive Extracts of Thevetia neriifolia - Madhumitha, G.; Mary Sara, A. (Asian Journal of Chemistry, 2010)
Antimicrobial activity of successive extracts of Thevetia neriifolia (Apocynaceae family) leaves in petroleum ether, benzene, chloroform, acetone and ethanol extract were investigated against a panel of bacteria and fungi using zone of inhibition by agar well diffusion method. The microorganisms used in test were Escherichia coli, Staphylococcus aureus, Pseudomonas vulgris, Klebsiella, Salmonella typhi, Bacillus subtilis, Salmonella paratyphi, Aspergillus niger and Aspergillus fumigatus. All extracts showed activities against bacteria and fungi.